Evaluation of Bcl 2 and Ki 67 expression in Chronic Lymphocytic Leukemia . - AL- Mudallal, Subh S.; Jasim, Huda N. (Journal of the Faculty of Medicine Baghdad, 2013)
Background :Chronic lymphocytic leukemia (CLL) is a low-grade B-lineage lymphoid malignancy. Both  Ki-67 which is a large nuclear protein associated with cell proliferation and Bcl-2 which is an anti-apoptotic protein which is associated with dysregulation of the intrinsic apoptotic pathway , were thoroughly investigated in many cancer patients particularly in hemopoietic malignancies .Patients, materials and methods: This retrospective study was conducted from November 2009 to May 2010 , on fifty formaline fixed paraffin embedded blocks of CLL cases retrieved from Medical City Teaching Hospital ; their age range was 39-75 years along with twenty control cases with benign reactive marrow , The sections of bone marrow biopsies were processed routinely in Al-Kadimiya teaching hospital laboratory and stained with H&E and the expression of  Bcl2 and Ki67 was evaluated by light microscope. Smears stained for Bcl2 were classified according to the scoring system used by  Soini Y,et al. ,whereas those stained for ki67 were evaluated by estimation the percentage of positive stained nuclei in the smears as was adopted by Diop S,et al.Results :    Immunohistochemical staining of CLL cases  revealed that 11/50  cases (22%) were positive for Ki67   showing  diffuse or granular nuclear brown  stain   ,  whereas  all control cases were negative for the marker . Those positive cases significantly correlate with modified Rai system   , Hb concentration  and platelet count ,but they  did  not  significantly  correlate with white blood cell count or lymphocyte % in the bone marrow and peripheral  blood smears .  Regarding Bcl 2  , 32/50 cases(64%) were positive for the marker showing diffuse  cytoplasmic brown reaction ,however no significant correlation was found between Bcl2 score  and modified Rai system or  with any of the mentioned hematological parameters .Finally , there was no significant correlation between Ki67 and Bcl2 expression .Conclusions: The  proliferative marker Ki-67 expression closely related to the clinical stage of  CLL patients , thus it could be considered as an informative and simple tool for assessing disease activity . On the other hand ,although  Bcl2 expression  was high in CLL patients but it did not related with the clinical stage of those patients . Finally .  Ki67 and Bcl2 were independent markers  and no correlation was found between them as they act on different pathways since ki67 is a proliferative and Bcl2 is an antiapoptotic marker.